Patient‐centred physical therapy is (cost‐) effective in increasing physical activity and reducing frailty in older adults with mobility problems: a randomized controlled trial with 6 months follow‐up. Issue 4 (4th December 2015) - de Vries, Nienke M.; Staal, J Bart; van der Wees, Philip J.; Adang, Eddy M. M.; Akkermans, Reinier; Olde Rikkert, Marcel G. M.; Nijhuis‐van der Sanden, Maria W. G.
Abstract: Background: Despite the well‐known health benefits of physical activity, it is a great challenge to stay physically active for frail–older adults with mobility limitations. The aim of this study was to test the (cost‐) effectiveness of a patient‐centred physical therapy strategy (Coach2Move) in which individualized treatment (motivational interviewing, physical examination, individualized goal setting, coaching and advice on self management, and physical training) is combined to increase physical activity level and physical fitness and, thereby, to decrease the level of frailty. Methods: A randomized controlled trial was performed in 13 physical therapy practices with measurements at 3 and 6 months. Eligible patients were aged 70 years or over and had mobility problems (i.e. difficulties with walking, moving, getting up and changing position from bed or chair to standing, or stair climbing). The primary outcome was physical activity (total and moderate intensity) in minutes per day. Secondary outcomes were as follows: frailty, walking speed and distance, mobility, and quality of life. Data were analysed using linear mixed models for repeated measurements. Healthcare costs and quality‐adjusted life years (QALYs) were computed and combined using net monetary benefit (NMB) for different willingness to pay thresholds. Data on costs, QALYs, and NMBs were analysed using linear mixed models. Results: One hundred and thirty patients participated in this study. At 6 months, the between‐group difference was significant for moderate‐intensity physical activity in favour of the Coach2Move group [mean difference: 17.9 min per day; 95% confidence interval (CI) 4.0 to 34.9; P = 0.012]. The between‐group difference for total physical activity was 14.1 min per day (95% CI −6.6 to 34.9; P = 0.182). Frailty decreased more in the Coach2Move group compared with usual care [mean difference: −0.03 (95% CI: −0.06 to −0.00; P = 0.027)]. Compared with usual treatment, the Coach2Move strategy resulted in cost savings (€849.8; 95% CI: 1607 to 90; P = 0.028), an improvement in QALYs, (0.02; 95% CI: 0.00 to 0.03; P = 0.03), and a higher NMB at every willingness to pay threshold. Conclusions: Older adults with mobility problems are able to safely increase physical activity in their own environment and reduce frailty. This study emphasizes both the potential cost‐effectiveness of a patient‐centred approach in the frail elderly and the importance of physical activity promotion in older adults with mobility limitations.